SPEECH ACTS IN PUBLIC FIGURES’ TWEETS ON ENVIRONMENTAL ISSUES - Stepanenko, K.; Karpenko, Y. (Studia Philologica, 2021)
This paper presents the detailed analysis and interpretation of the main speech acts used in the tweets of public figures. Our novel findings discover the major types of the speech acts found in the utterances of public figures related to the environment. Based on the studies of numerous scholars and rich theoretical background on speech acts theory, the study touches the aspect of global problems depicted in media discourse with regard to the pragmatic reference to the audience reaction. The methodology of this article begins with the task to collects the data in the English Twitter Corpus from the utterances of renown environmental activists. The highlight of the publication is the classification of these utterances supported by the numerical data. In addition to the illocutionary aspect, perlocutionary effect was identified proceeding from the reaction count. Along with a single and complex speech act, the authors identified the meaning of a complex speech act within the Twitter social networking service. Another major feature of the publication is identifying reversed speech acts used by the public figures for highlighting the importance of the topic raised on their microblogs. The present research explores the perlocutionary effect of the tweets by counting replies on tweets, quote tweets and likes. Having applied quantitative methods, the leading environmental topics were identified judging by the response of the audience. Calculated data is extensively used in the research to show the considerable impact of specific topics on the audience. This research will contribute to a deeper understanding of pragmatic study of social media for more profound arrangement of public figures’ speeches which can be translated to a schema for creating targeted social media discourse. Keywords: social media discourse, environmental discourse, public figures’ utterances, speech acts, tweet, illocutionary act, perlocutionary effect.